Gene duplication captures morph-specific promoter usage in the evolution of aphid wing dimorphisms - Omid Saleh Ziabari; Fangzhou Liu; Kevin D. Deem; Xiaomi Liu; Akhil Kholwadwala; Jennifer A. Brisson (Proceedings of the National Academy of Sciences, 2025)
Understanding how morphology evolves requires identifying the types of mutations that contribute to changes in development. We integrated comparative genomics and transcriptomics to reconstruct the evolution and regulation of follistatin paralogs in relation to the evolution of aphid winged and wingless morphs. We find that different pea aphid follistatin duplicates play an essential molecular role in both the male and female wing dimorphisms, linking the genetic and environmental control of morph determination in each sex, respectively. We also find that an ancestral follistatin gene likely had multiple promoters and that the follistatin duplicates that evolved wingless-specific expression retained only the ancestral wingless-specific promoter. Our work provides a roadmap for how alternative promoter usage and subsequent gene duplication can enable the evolution of animal form.